Географічне поширення видів роду Euphrasia L. (Orobanchaceae Vent.) в Україні - Перегрим, О.М.; Перегрим, М.М. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Анализируется хорология 21 вида рода Euphrasia флоры Украины. Рассмотрены ареал каждого вида и географическое распространение в Украине. Уточнена южная граница «циркумполярного кольца» рода на территории Украины. Chorology of 21 species of Euphrasia in the Ukrainian flora is analyzed and generalized. The ranges of each species and descriptions of geographical distribution in Ukraine are provided. The southern border of the «curcumpolar ring» of the total generic range is detalized and outlined.